Breast Cancer Awareness among Bandung Adolescents - Mutiara Aini Majid; Holis Abdul Holik; Arifudin Achmad; Achmad Hussein Sundawa Kartamihardja (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2022)
Most breast cancer patients in Indonesia experienced a delay in their diagnosis due to a lack of awareness and other factors. Female adolescents are the key population for an educational intervention to raise breast cancer awareness. This study assessed knowledge of breast cancer risk factors, signs, and symptoms, attitudes toward breast cancer prevention, barriers in breast cancer screening, and behavior regarding breast cancer awareness among female adolescents in Bandung using the Breast Cancer Awareness Scale – Indonesia (BCAS-I) instrument. Among 371 female high school and undergraduate students, 53.1% of them had limited knowledge about breast cancer risk factors, and 99.2% of these respondents had negative behaviors. However, most of them understood the early breast cancer signs and symptoms (89.8%) and had positive attitudes toward seeking health support (98.7%). Preference of health information sources and educational level are the significant factors for breast cancer awareness. Our initial assessment may provide the basis for further research and surveys on a larger scale to develop breast cancer prevention educational materials appropriate for young female populations.